Aplicação do método QuEChERS no preparo de amostra de águas superficiais para determinação de atrazina, desisopropilatrazina (DIA), desetilatrazina (DEA) e carbendazim por LC-DAD - Gabardo, Renata Prussak (2018)
Brazil is the largest consumer of pesticides in the world, mainly because it has agriculture as the basis of its economy, causing many of these to be found in the environment. In Paraná, the Paraná 3 Watershed consumes more pesticides than the average value of the state, provoking interest in evaluating the presence of these pesticides in several environmental matrices, including water. However, the determination of pesticide residues in surface waters is a challenge due to the presence of interferents and the low concentrations of the analytes, leading to the analysis of new analytical techniques. Sample cleaning through the QuEChERS method for the determination of pesticides in food has been widely explored, but little evaluated in aqueous samples. The aim of this study was to evaluate the potential of concentration and cleaning of aqueous samples for the determination of atrazine, deisopropyl-atrazine (DIA), deethyl-atrazine (DEA) and carbendazim in surface water. An analytical method by LC-DAD was developed and determinedseveral parameters of merit for the determination of atrazine, DIA, DEA and carbendazim, reaching values of limit of quantification (LOQ) of 0.010 mg L-1, with r2 of 0.99. Applying the QuEChERS method for preparation of surface water samples from BP3, it was possible to verify that the modified QuEChERS method allowed to perform the concentration of these on the order of 25 times. For samples fortified with 5, 7 and 10 µg L-1, the results were 91.8 to 113.9% for ATZ, 67.3 to 71.9% for DIA and 62.8 to 86.0 % for the DEA. However the application of the method developed for the analysis of samples of the rivers of interest, no signals were verified referring to the analytes. In order to certify their absence in the samples, SPE tests were conducted on Oasis-HLB cartridges, comparing the recovery of samples in ultra pure water and one of the rivers, with and without fortification. Fortified samples, concentrated 750 times, indicated the presence of DEA, in the order of 0.30 µg L-1, below the capacity of determination of the evaluated QuEChERS method, but the other analytes were not detected. It was observed with the samples fortified with 5, 7 and 10 µg L-1, with a concentration of 25 times, that the percentages of recovery were higher for the QuEChERS technique than those obtained by the SPE technique, however the superior capacity of concentration of SPE technique also favors its use for the determination of the analytes in the observed environmental concentrations of these pesticides in the evaluated samples, and a further improvement of the QuEChERS technique is required for its application for this purpose.